2011
DOI: 10.1007/s10072-011-0595-3
|View full text |Cite
|
Sign up to set email alerts
|

Sacculocolic reflex in patients with dementia: is it possible to use it for early diagnosis?

Abstract: Alzheimer disease (AD) is a progressive, irreversible entity associated with behavioral changes, memory loss and disturbance of daily life activities. Current diagnostic tools can detect neuronal degeneration in AD only after irreversible damage that already existed. Vestibular evoked myogenic potentials (VEMP) test utilizes the sacculocolic reflex arc and has been used in neuro-otology practice for many years. In this study, we aim to determine if VEMP can be used for diagnostic purposes at the earliest stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…In fact, latency delay was significantly prevalent in early PD while low amplitude and absence were more observed in late PD, this latter data being consistent with previous reports on cVEMP (Potter-Nerger et al, 2012). This finding may indicate a pattern of progression of VEMP abnormalities, as the disease progresses, as observed in other neurological diseases, as multiple sclerosis (Patkò et al, 2007;Magnano et al, 2014) and AD (Birdane et al, 2012). It is possible that the decrease in the net number of vestibular neurons, which occurs in established PD (Delwaide et al, 1993), is progressively reflected by reduction of the amplitude of the reflex until its disappearance.…”
Section: Vemps: Early Pd Versus Late Pdsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, latency delay was significantly prevalent in early PD while low amplitude and absence were more observed in late PD, this latter data being consistent with previous reports on cVEMP (Potter-Nerger et al, 2012). This finding may indicate a pattern of progression of VEMP abnormalities, as the disease progresses, as observed in other neurological diseases, as multiple sclerosis (Patkò et al, 2007;Magnano et al, 2014) and AD (Birdane et al, 2012). It is possible that the decrease in the net number of vestibular neurons, which occurs in established PD (Delwaide et al, 1993), is progressively reflected by reduction of the amplitude of the reflex until its disappearance.…”
Section: Vemps: Early Pd Versus Late Pdsupporting
confidence: 90%
“…Similarly to PD, higher rates of cVEMP abnormalities were found in patients with Alzheimer's Disease (AD, Birdane et al, 2012), which, like PD, is also thought to start in the brainstem (Simic et al, 2009). In this regard, neurodegeneration in PD is thought to occur in a stereotyped temporo-spatial manner, involving the brainstem in the earliest stages, followed by degeneration of substantia nigra and basal ganglia, which is associated with the motor symptoms leading to clinical diagnosis (Wolters and Braak, 2006).…”
Section: Vemps: Pd Patients Versus Controlsmentioning
confidence: 96%
“…Furthermore, synaptic changes have been reported in the vestibulocerebellar systems of AD patients [23], as well as neurofibrillary tangles in the lateral vestibular nucleus [24], and the expression of beta-amyloid has been demonstrated in the vestibular nuclei of a mouse transgenic model of AD [25]. Birdane et al [21] have suggested that deficits in the sacculo-collic reflex, one of the subtypes of vestibular reflexes, may even serve as an early diagnostic marker of AD. Concidentally, many studies in both animals and humans over the last 2 decades, have shown that damage to the peripheral vestibular system causes deficits in memory and attention [26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Box 913, Dunedin, New Zealand; Tel: 0064 3 4795747; Fax: 0064 3 4799140; E-mail: paul.smith@stonebow.otago.ac.nz A number of studies have suggested that AD is associated with neurodegeneration of the vestibular system, which senses acceleration of the head and generates eye movement and postural reflexes to maintain visual acuity and balance during head movement. Patients with AD have been reported to exhibit deficits in the vestibulo-spinal reflexes [e.g., 21,22]. Furthermore, synaptic changes have been reported in the vestibulocerebellar systems of AD patients [23], as well as neurofibrillary tangles in the lateral vestibular nucleus [24], and the expression of beta-amyloid has been demonstrated in the vestibular nuclei of a mouse transgenic model of AD [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation